A VALUE OF BADMINTON GAME IN HUMAN LIFE - Wakradkar, Mahesh Raoji (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In ancient times, food, clothing and shelter were considered basic needs for human life. Nowadays the most important part attached in basic needs changes that are the basic needs include health and education. Game is considered to be a unique element in human life because of it helps in maintaining physical balance, controlling heart and cardiovascular diseases, controlling diabetes, maintaining wellness, improving blood circulation, relieving fatigue and reducing lack of control. Individuals who participate in sports can balance physical and mental development, keep their health and strengthen their bones. As soon as the word game or competition is uttered, it is considered as a true sportsman who gets excited because the sportsman has certain qualities, such words, materials, field etc. are seen that the body is ready to play and a new spirit is created in them. Sports and competition play an important role in a person's life to achieve personal, academic, social and intellectual development of the athlete as well as physical health, mental abilities and social skills. Athletes are not only playing sports, but sports also help maintain a healthy body by improving cardiovascular fitness, strength and flexibility, reducing the risk of chronic diseases, improving physical parameters, developing qualities such as speed and agility, muscular strength, agility, and strength.